PERILAKU NASABAH DALAM BERTRANSAKSI DENGAN BANK SYARIAH DI KOTA MALANG - Wijayanti, Anita; Kurniawati, Eris Tri (Departmen Vocational Financial and Banking, 2009)
Â In this current year, Islamic commercial banking industries have grown rapidly. They are involved in a tight competition. The competition is not only happened between Islamic commercial banking companies but also with conventional banking companies. The reasons of customers to do a transaction with Islamic commercial banking companies are needed to be understood by either practitioners or scholars. The research aim is to investigate the variables which affect consumerâ€™s behavior in terms of doing transactions in Islamic commercial banking companies in Malang. Theory of planned behavior is used in this research as a basic frame work for analyzing those variables.The population of this research is all of Islamic commercial banking companies which are located in Malang. Sample is collected by using probability sampling method. In terms of answering the research question, multiple regressions are used. F-test and t-test are used in order to test the hypotheses.The result of this research shows that the three independent variables (attitude towards behaviour, subjective norms, and perceived control behaviour) has a significant influence either as partial or simultaneous goes together with the variable of the consumerâ€™s behavior in terms of doing transactions in Islamic commercial banking companies in Malang. The most significant variable from the three independent variables is attitude towards behaviour (68,1%).Keywords: transaction, Theory of Planned Behavior, Islamic banking